PENINGKATAN HASIL BELAJAR TEMATIK TERPADU MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SD - Wahyu Septina Rada Amra; Mai Sri Lena (STKIP Subang, 2022)
This study aims to increase student learning outcomes by using a problem based learning model in class V at SDN 12 Gunung Malelo Pesisir Selatan. This research is a type of CAR using a qualitative and quantitative approach. This research was conducted in 4 stages, namely: (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection. the results of observations of RPP in the first cycle which has a percentage of 81.94% with good qualifications (B) and an increase in the second cycle which has a percentage of 94.44% with very good qualifications (SB). Based on the results of observations of teacher activities in the first cycle, which has a percentage of 85.71% with good qualifications (B) and an increase in the second cycle which has a percentage of 96.42% with very good qualifications (SB). While on the results of observing the activities of students in the first cycle, which has a percentage of 85.71% with good qualifications (B) and there is an increase in the second cycle with a percentage of 96.42% with very good qualifications (SB). Based on the explanation above, it can be concluded that research conducted using this problem based learning model can improve student learning outcomes in class V Elementary School.